Analysis on Students’ Performance to Promote Gender Equality in Creative Fashion Design - Amos, Emmanuel; Essel, Harry Barton; Fobiri, George K.; Ibrahim, Mohammed (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
The fashion industry has prospects and it can help to project the economy to compete with the international market. However, the extent of gender imbalance emerging from the Fashion Department of Kumasi Technical University is becoming a threat to the future of the industry. This paper is aimed at creating awareness of the extent of gender imbalance and promoting the inclusion of more male fashion students in fashion institutions. This was achieved by conducting an analysis of gender performance in Creative fashion design processes. The study employed educational Design and Quantitative research methods with a descriptive style of analysis. With a sample size of n=191, a structured questionnaire was distributed to participants on different occasions during class hours to gather relevant data for the study. The results showed that, though the female students were more than the male students,  the male students performed better than the female students in terms of creative fashion design processes. Most of the students were of the opinion that the famous fashion designers in history and the present day are men. Also, most of the students responded that the best fashion designers in their locality are men. The study recommends that society needs to be educated and encourage more male students to take up fashion as a career.